Methods for the development of the initial material in the process of winter durum wheat breeding and their efciency - N. E. Samofalova; N. P. Ilichkina; T. S. Makarova; О. А. Dubinina; О. А. Kostylenko; A. S. Kameneva; Т. G. Derova (Зерновое хозяйство России, 2020)
The success in development of winter durum wheat varieties with a high adaptability to abio- and biotic stress conditions, large and stable productivity is usually determined by the diversity of initial material and methods for its preparation. The most efective method to develop genetic variability among winter durum wheat varieties and other grain crops is hybridization (intraspecifc, interspecifc, and intergeneric). The purpose of the current study was to evaluate the breeding material obtained in the breeding process among intraspecifc and interspecifc hybrids of diferent types of hybridization according to the main economically valuable traits and properties and to identify a more efective method/type of hybridization. The object of the study was 28 breeding lines of durum winter wheat identifed from the following types of hybridization: the 1st type was T. winter durum x T. winter durum (paired and gradual), 7 samples; the 2nd  type was T. winter durum x T. winter durum (paired), 3 samples; the 3rd  type was F1  (T. winter durum x. T. winter  durum) x T. winter durum, 4 samples; the 4th  type was T. winter aestivum x T. winter durum (direct and reverse), 7 samples; the 5th  type  was F1  (T. winter aestivum x. T. winter durum) x T. winter durum (triple), 7 samples. According to the comparative study results of  breeding material of intraspecifc and interspecifc hybrids, it has been found that intraspecifc paired and gradual hybridization, which  provided high productivity and grain quality was a more efective method for developing of winter durum wheat varieties. The rest  types of crossings, primarily interspecifc, could be helpful to obtain initial material with a high level of winter tolerance, resistance to lodging and diseases, for their further use in intraspecifc gradual hybridization.